Gender bias and stereotypes in Australian, Singaporean and Turkish mathematics textbooks - İNCİKABI, Lütfi; ULUSOY, Fadime (Turkish Journal of Education, 2019)
This cross-national study aimed to examine gender bias and stereotypes in Australian, Singaporean and Turkish elementary mathematics textbooks. Content analysis approach was used to provide descriptive statistics about the number of male/female and gender-neutral characters in the textbooks. Findings indicated that total frequencies in textbook contents including no gender bias was under nine percent in all textbooks. No gender bias was more prevalent across the grade levels in Australian textbooks. Singaporean mathematics textbooks had more discrepancy between the percentages of boys’ and girls’ representations than the representations in Turkish and Australian textbooks. In terms of math-gender stereotypes, all textbooks across grade levels were generally neutral. Social roles in mathematics textbooks across the countries had more variation for men than women with higher frequencies in all countries. The masculine roles were commonly attributed to men with more technical and intellectual tendency while domestic roles were ascribed to females.
Keywords: 5. Gender equality; 4. Education; 10. No inequality